Direct meta‐C−H Perfluoroalkenylation of Arenes Enabled by a Cleavable Pyrimidine‐Based Template. Issue 44 (11th July 2019) - Brochetta, Massimo; Borsari, Tania; Bag, Sukdev; Jana, Sadhan; Maiti, Siddhartha; Porta, Alessio; Werz, Daniel B.; Zanoni, Giuseppe; Maiti, Debabrata
Abstract: The development of efficient and mild methods for the synthesis of organofluorine compounds is of foremost interest in various fields of chemistry. A direct pyrimidine‐based selective meta ‐C−H perfluoroalkenylation of arenes involving several commercially available perfluoroolefins is described. The synthetic versatility of the protocol is demonstrated by an extensive substrate scope including different benzylsulfonyl, alkylarene and phenylacetic acid scaffolds. The generality of this methodology including the meta ‐C−H perfluoroalkenylation of Ibuprofen, the facile cleavage of the directing group and gram‐scale reactions are presented. Abstract : Right to the point : A palladium(II)‐catalyzed meta ‐selective C−H perfluoroalkenylation of arenes utilizing readily available fluorinated olefins is described. The practicability of this transformation has been demonstrated by selective perfluoroolefination of the pharmaceutical Ibuprofen.